Study of the coastal sediments of the Loutraki gulf area - ΚΑΡΑΛΗ-ΒΟΥΔΟΥΡΗ, Α.; ΛΕΙΒΑΔΙΤΗΣ, Γ.; ΜΕΤΤΟΣ, A. (Bulletin of the Geological Society of Greece, 2018)
The study of the sedimentological and mineralogical characteristics of the coastal sediments in the Loutraki gulf, included analyses of a large number of samples, that is granulometry, thin section study and x-ray examination. From these data the granulometry paramètres were assessed such as mean grain size, standard deviation σ, skewness SK, and kurtosis KG of the sediments. The study of the sedimentological parameters based on the mean grain size the offshoreline is covered by coarse grain sand, whereas the tidal zone indicates a high energy environment. The longshoredrift is from Ν to S. Most of the sand is loosely graded in the nearschore area, medium graded in the foreshore area and well graded in the backshore area. Their constant declination indicates a trend for a better gradation of sediments southwards. The latter combined with the mean grain size indicate a reduction of kinetic energy from Ν to S. In addition, the beachrocks, were studied together with their, elevation and their mineral composition .